Hierarchical structure pitch-based carbon fiber skeleton electrothermal base paper and preparation process and preparation method thereof

By using the combination of hierarchical structured asphalt -based carbon fiber skeleton and conductive carbon black in the carbon fiber paper, the problem of poor and poor thermal conductivity of carbon fiber paper is solved, and efficient electrical conversion and mechanical performance improvement are achieved.

CN119372958AActive Publication Date: 2025-01-28SHAANXI UNIV OF SCI & TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411790678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Existing carbon fiber paper has problems of vulnerability and poor thermal conductivity, which limits its application in the field of fuel cells.

Method used

The preparation process of hierarchical structured asphalt -based carbon fiber osteogenesis is used to optimize the mechanical performance and conductive performance of carbon fiber through the layered formation of the surface layer and the middle layer, combined with conductive carbon black and asphalt -based carbon fiber.

Benefits of technology

It improves the thermal conductivity, strength, and toughness of carbon fiber paper, enhances its ability to afford the impact and pressure of external forces, and achieves high response and high heating efficiency at low voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372958A_ABST
    Figure CN119372958A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of specialty paper, carbon fiber composite paper and electric heating materials, in particular to pitch-based carbon fiber skeleton electric heating body paper with a hierarchical structure and a preparation process of the pitch-based carbon fiber skeleton electric heating body paper with the hierarchical structure. The carbon fibers with different lengths, the aramid pulp, the aramid precipitation and the carbon black are ingeniously combined to form a sandwich hierarchical structure, the carbon black is introduced into the surface layer to reduce insulation fiber resistance, stabilize heating power, prevent electric heat dissipation and improve heating uniformity, the long carbon fibers adopted by the middle layer can provide a current conductive path, and the service life of the carbon fibers is prolonged. The overall utilization rate of carbon fibers is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special paper, carbon fiber composite paper and electric heating paper preparation, and specifically to a hierarchical asphalt-based carbon fiber skeleton electric heating base paper and a preparation process thereof. Background Art

[0002] Carbon fiber paper can be traced back to the 1960s, when a US company developed the first batch of carbon fiber paper and used it for special parts in the aviation field. Carbon fiber itself has extremely high strength and modulus. The carbon fiber paper made of it has excellent durability and bending resistance while maintaining lightness and thinness. It is light and easy to carry and use. At the same time, carbon fiber has excellent conductivity, which can meet the requirements of electronic products for electrostatic protection and electromagnetic shielding, and can also be used as electrode materials; in addition, it has good stability and can work stably in high temperature environments. It is suitable for insulation and heat preservation materials of high-temperature furnaces, heat exchangers and other equipment. It is corrosion-resistant, acid-resistant and alkali-resistant, and can maintain stable performance in different chemical environments.

[0003] There are two main methods for preparing carbon fiber paper: wet method and dry method. The wet method is to mix carbon fiber and raw materials such as resin to make a pulp suspension, and then form it through processes such as papermaking, pressing, and drying, followed by impregnation, pre-oxidation, carbonization, and graphitization. The dry method is to directly compress or pyrolyze carbon fiber and other raw materials under conditions such as hot pressing or pyrolysis to form carbon paper. For example, CN103628350B prepares a flame-retardant carbon fiber electric heating paper by mixing carbon fiber with raw materials such as wood glue and gelatin, and through wet papermaking processes such as papermaking, pressing, and drying, thereby solving the problems of traditional carbon fiber paper such as resistance, uneven heating, and easy breakage and tearing; CN102465475A mixes polyacrylonitrile-based carbon fiber with serpentine cotton wool, and through wet papermaking process, successfully prepares industrial high-temperature carbon fiber electric heating paper, overcoming the problem of limited heating temperature due to the low carbonization temperature of pulp when traditional short-cut carbon fiber is mixed with pulp for papermaking; CN110129992B prepares a carbon fiber paper for fuel cells by graphitizing carbon fiber, dry papermaking to make preforms, and through processes such as carbonization and deposition, thereby solving the problems of carbon fiber not being easy to break up, slow water filtration, and harmful liquid discharge during wet papermaking.

[0004] At present, carbon fiber paper is widely used in aerospace, automotive industry, electronic products, medical equipment and sporting goods. In the field of fuel cells, as a key substrate material for the gas diffusion layer, it plays an important role in supporting, collecting current, conducting gas and removing reactant water. However, due to the high cost, easy damage and poor thermal conductivity of traditional carbon fiber paper, the development of the domestic carbon fiber paper industry is limited. Summary of the invention

[0005] In view of the problem that carbon fiber paper in the prior art is easily damaged and has poor thermal conductivity, the present invention provides a hierarchical asphalt-based carbon fiber skeleton electric heating base paper and a preparation process and a preparation method thereof.

[0006] The present invention is achieved through the following technical solutions: A process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper comprises the following steps: S1, preparing a surface paper web: weighing aramid pulp, aramid precipitate, conductive carbon black, carbon fiber and PEO dispersion, mixing and dispersing to obtain a mixed system slurry A, and then forming a surface wet paper web B by slurry dilution, turbulent homogenization and negative pressure dehydration; Preparation of middle layer paper web: weighing carbon fiber, aramid precipitate and PEO dispersion, mixing and dispersing to obtain mixed slurry C, and then forming carbon fiber middle layer wet paper web D by dilution, water addition, turbulent homogenization and negative pressure dehydration; S2, overlapping the middle layer wet paper web D and the surface layer wet paper web B, and then cold pressing and dehydrating to obtain a layered structure paper web E; S4, subjecting the hierarchical structure paper web E to vacuum drying and hot pressing bonding to obtain a hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper F.

[0007] Preferably, in S1, when preparing the surface paper web, the aramid pulp is para-aramid fiber, the beating degree is (45-48)°SR, the specific surface area is (9-11) m² / g, and the total absolute dry weight is (0.26-0.27) g; The aramid precipitate is a differentiated product of meta-aramid fiber, with a beating degree of (42-45)°SR, a moisture content of (70-85)%, and a total absolute dry weight of (3.64-3.65) g; The carbon fiber is pitch-based carbon fiber with a fiber length of (3-4) mm, a fiber diameter of (6-10) μm, and a total absolute dry weight of (0.37-0.38) g; the conductive carbon black mass is (0.30-0.50) g, and the conductivity is (0.20-0.50) S·cm -1 ; The concentration of PEO dispersion is (10-15) g / L, and the measured volume is (10.00-11.00) mL.

[0008] Preferably, in S1, when preparing the surface paper web, the decomposition speed is 25000-30000 rpm; The amount of water added for dilution is (2.0~3.0)L; Turbulent homogenization is (8-10) times; Water is vacuumed through a (80-100) mesh forming net, the vacuum degree is 0.080-0.098 MPa, and the vacuum pumping time is (20-25) s.

[0009] Preferably, in S1, when preparing the middle layer paper web, the carbon fiber is asphalt-based carbon fiber, the fiber length is (7-8) mm, the fiber diameter is (6-10) microns, and the total absolute dry weight is (0.87-0.88) g; The aramid precipitate is a differentiated product of meta-aramid fiber, with a beating degree of (45-50)°SR, a moisture content of (85-92)%, and a total absolute dry weight of (2.18-2.19) g; The concentration of the PEO dispersion is (10-15) g / L, and the measured volume is (10.00-11.00) mL.

[0010] Preferably, in S1, when preparing the middle layer paper web, the deflaking rotation speed is 25000-30000 rpm; The amount of water added for dilution is (2.0~3.0)L; Turbulent homogenization is (8-10) times; Water is vacuumed through a (80-100) mesh forming net, the vacuum degree is 0.080-0.098 MPa, and the vacuum pumping time is (20-25) s.

[0011] Preferably, in S2, when overlapping, the middle layer wet paper web D is transferred between the two surface layer wet paper webs B.

[0012] Preferably, in S2, during the cold pressing dehydration, absorbent felt pads are used on both the upper and lower sides of the superimposed wet paper webs, the pressing pressure is (8.5-10.5) MPa, and the pressing time is (5-10) min.

[0013] Preferably, in S3, during the vacuum drying treatment, the temperature is (105-120)°C, the vacuum degree is (0.7-0.9) MPa, and the time is (10-15) min.

[0014] Preferably, during the thermal compression bonding process, the temperature is (180-200)°C, the pressure is (12-15) MPa, and the time is (15-20) min.

[0015] A product obtained according to the process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper.

[0016] Compared with the prior art, the present invention has the following beneficial effects: First of all, the present application discloses a process for preparing hierarchical asphalt-based carbon fiber skeleton electric heating base paper, including surface layer paper preparation, middle layer preparation, hierarchical structure paper preparation and hierarchical structure paper reinforcement. Compared with the disclosed preparation technology, the present application designs the formula of the heating surface layer and the conductive middle layer through layered forming, so that they are distinguished according to the contact resistance, which is more conducive to the mechanical properties and conductive properties of carbon fiber, and shows significant advantages in electrical and thermal conductivity, high strength and high modulus, and hierarchical heat control.

[0017] Secondly, the hierarchical structure in the present application enables each layer to assume different functions. Adding conductive carbon black to the surface paper can improve the efficiency and uniformity of electrothermal conversion. Combined with the filling effect of conductive carbon black on the gaps between fibers, the structural density is further improved, making it more able to withstand external impact and pressure and not easily damaged.

[0018] The asphalt-based carbon fiber skeleton of the middle layer is preferably made of fibers with a larger aspect ratio, which can easily reduce contact resistance and form a stable conductive network. While enhancing the strength and toughness of the paper, it also improves the electrical conductivity of the carbon fiber and the heat generation utilization rate of the carbon fiber distributed throughout the carbon fiber paper. The surface layer and the middle layer work together, and the overall performance of the carbon fiber composite paper is reasonably designed.

[0019] Furthermore, conductive carbon black has good electrical conductivity, which further improves the overall electrical conductivity of carbon fiber paper, so that during the power-on process, electrical energy can be more efficiently converted into thermal energy, thus better improving the heating efficiency. At the same time, conductive carbon black can fill the gaps in carbon fiber paper to build a uniform conductive path to avoid excessive local current, adjust thermal conductivity to balance thermal conductivity and prevent heat accumulation, thus improving the uniformity of paper heating.

[0020] Furthermore, the asphalt-based carbon fiber skeleton plays a key supporting role in the hierarchical structure. This skeleton structure is similar to a stable frame that can limit the disordered movement of the internal parts of the paper. When the current passes through to generate heat, the carbon fiber skeleton can keep the relative position of each part stable, avoiding the fluctuation of electrothermal performance caused by local structural changes, thereby reducing electrothermal drift.

[0021] Furthermore, the present invention achieves high response and high heating efficiency under low voltage without adding almost any additional components and costs through the regulation of the interlayer structure of carbon fiber and the introduction of carbon black heating functional components, and has high engineering potential; at the same time, the design ideas and structural innovations of the present invention can be extended to other types of electrothermal materials, and have reference value for further constructing electrothermal materials with similar principles. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a flow chart of a process for preparing a hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper of the present invention; Figure 2 The carbon fiber paper containing 0.3 g of carbon black obtained in Example 1; Figure 3 is a SEM magnified image of the cross section of the carbon fiber paper obtained in Example 1; Figure 4 is a SEM image of the surface of the carbon fiber paper obtained in Example 1; Figure 5is a graph showing the change of the temperature of the carbon fiber paper in Example 1 as the voltage increases; Figure 6 The carbon fiber paper containing 0.5 g of carbon black obtained in Example 2; Figure 7 is a SEM magnified image of the cross section of the carbon fiber paper obtained in Example 2; Figure 8 is a SEM image of the surface of the carbon fiber paper obtained in Example 2; Fig. 9 is a graph showing the change of the temperature of the carbon fiber paper in Example 2 as the voltage increases; Fig.10 is a graph showing the change in temperature of the carbon fiber paper in Example 1 as the voltage increases and decreases; Fig.11 is a graph showing the change in temperature of the carbon fiber paper in Example 2 as the voltage increases and decreases; Fig.12 This is the XRD performance test of carbon fiber paper in implementation cases 1 and 2. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0024] The present invention discloses a hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper and its preparation process, referring to Figure 1 , including the following steps: S1, preparing the surface paper web: weighing a certain amount of aramid pulp, aramid precipitate, conductive carbon black, carbon fiber and PEO dispersion and sequentially adding them into a deflaking cylinder, obtaining a mixed system slurry A through deflaking, and then forming a surface layer wet paper web B through slurry dilution, turbulent homogenization and negative pressure dehydration.

[0025] Among them, the aramid pulp is para-aramid fiber, with a beating degree of (45-48)°SR, a specific surface area of ​​(9-11) m² / g, and a total absolute dry weight of (0.26-0.27) g; the aramid precipitate is a differentiated product of meta-aramid fiber, with a beating degree of (42-45)°SR, a moisture content of (70-85)%, and a total absolute dry weight of (3.64-3.65) g; the carbon fiber is asphalt-based carbon fiber, with a fiber length of (3-4) mm, a fiber diameter of (6-10) microns, and a total absolute dry weight of (0.37-0.38) g; the mass of conductive carbon black is (0.30-0.50) g, and the conductivity is (0.20-0.50) S·cm-1; the concentration of polyethylene oxide (PEO) dispersion is (10-15) g / L, and the measured volume is (10.00-11.00) mL.

[0026] The disintegration speed is 25000~30000 rpm; the dilution water amount is (2.0~3.0) L; the turbulent homogenization is (8~10) times, and the vacuum water is pumped through the (80~100) mesh forming net, the vacuum degree is 0.080~0.098MPa, and the vacuum water pumping time is (20~25) s.

[0027] Preparation of an intermediate layer paper web: weighing carbon fiber, aramid precipitate and PEO, mixing and decomposing to obtain a mixed slurry C, and then forming a carbon fiber intermediate layer wet paper web D by dilution and water addition, turbulent homogenization and negative pressure dehydration; wherein the carbon fiber is asphalt-based carbon fiber, the fiber length is (7-8) mm, the fiber diameter is (6-10) microns, and the total absolute dry weight is (0.87-0.88) g; the aramid precipitate is a differentiated product of meta-aramid fiber, the beating degree is (45-50) °SR, the water content is (85-92)%, and the total absolute dry weight is (2.18-2.19) g; the concentration of the polyethylene oxide (PEO) dispersion is (10-15) g / L, and the measured volume is (10.00-11.00) mL; the decomposition speed is 30000 rpm; the amount of water added for dilution is (2.0~3.0) L; the turbulent homogenization is (8~10) times, and the vacuum water is pumped out through the (80~100) mesh forming net, and the vacuum water pumping time is (20~25) s.

[0028] S2, preparing hierarchical structure paper, overlapping the middle layer wet paper web D and the surface layer wet paper web B, and then cold pressing and dehydrating to obtain the hierarchical structure paper web E. Specifically, the middle layer wet paper web D is transferred to the middle of the two surface layer wet paper webs B, and then cold pressing and dehydrating is performed after overlapping to obtain the paper web E; wherein, when using a cold press machine for cold pressing and dehydration, absorbent felt pads are required on the upper and lower sides, the pressing pressure is (8.5-10.5) MPa, and the time is (5-10) min.

[0029] S3, hierarchical paper reinforcement: the paper web E is vacuum dried in the drying section of the paper sheet former and hot-pressed and bonded on a flat vulcanizer to obtain a hierarchical asphalt-based carbon fiber skeleton electric heating base paper F; wherein, during the vacuum drying treatment, the temperature is (105-120)°C, the vacuum degree is (0.7-0.9) MPa, and the time is (10-15) min; the hot-pressing bonding temperature of the flat vulcanizer is (180-200)°C, the pressure is (12-15) MPa, and the time is (15-20) min.

[0030] The present invention utilizes a clever combination of carbon fibers of different lengths, aramid pulp, aramid precipitation and carbon black to form a "sandwich" hierarchical structure. The introduction of carbon black into the surface layer reduces the resistance of the insulating fiber, stabilizes the heating power, prevents electric heat dissipation, and improves the heating uniformity. The long carbon fibers used in the middle layer can provide a current conduction path, thereby improving the overall utilization rate of the carbon fibers.

[0031] Example 1 Step 1, weighing 0.2636g of aramid pulp with a beating degree of 45°SR and a specific surface area of ​​10m² / g, weighing 3.6486g of aramid precipitate with a beating degree of 45°SR and a water content of 85%, weighing 0.30g of conductive carbon black with a conductivity of 0.20S·cm-1, weighing 0.3763g of carbon fiber with a fiber length of 3mm and a fiber diameter of 6 microns and 10.00mL of a PEO dispersion with a concentration of 10g / L and adding them into a deflaking cylinder in sequence; obtaining a mixed system slurry A by a deflaking treatment at a rotation number of 30000 rpm, and then adding 3.0L of dilution water, performing 10 times of turbulent homogenization and 25 seconds of negative pressure dehydration on an 80-mesh forming wire to form a surface layer wet paper web B.

[0032] 0.8782g of carbon fiber with a fiber length of 7mm and a diameter of 6 microns was weighed, and 2.1873g of aramid precipitate with a beating degree of 45°SR and a water content of 85% was weighed and mixed with 10.00mL of a PEO dispersion with a concentration of 10g / L. A mixed slurry C was obtained by degassing at 30000rpm, and then 3.0L of dilution water was added, 10 times of turbulent homogenization and 25 seconds of negative pressure dehydration on an 80-mesh forming wire were performed to form a surface wet paper web D.

[0033] Step 2: transfer the middle layer wet paper web D to the middle of the two surface layer wet paper webs B, overlap them, pad them with absorbent felt on the top and bottom, and use a cold press with a pressing pressure of 9.0 MPa to dehydrate for 5 minutes to obtain paper web E.

[0034] Step 3, vacuum dry the paper web E in the drying section of a paper sheet former at a temperature of 105°C and a vacuum degree of 0.8MPa for 10 minutes; and hot-press and bond it in a flat vulcanizer at a temperature of 200°C and a pressure of 13MPa for 15 minutes to obtain a hierarchical asphalt-based carbon fiber skeleton electric heating base paper F.

[0035] The hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper obtained in this embodiment (such as Figure 2 , 3 , 4), the paper weight is 40g / m 2 , thickness is 0.142mm, square resistance is 18.16Ω, tensile strength is 1.08kN / m, paper weight is 4.37g, it can be heated to 193℃ at 12V voltage, heating rate is 2.05℃ / s, and it has high electric heating function under low voltage. Figure 5 The surface temperature of carbon fiber paper containing 0.3g carbon black increases with the increasing voltage. At 4V, the surface temperature can reach 39℃; at 8V, the surface temperature can reach 99℃; at 12V, the surface temperature can reach 193℃.

[0036] Example 2 Step 1, weighing 0.2640g of aramid pulp with a beating degree of 45°SR and a specific surface area of ​​10m² / g, weighing 3.6457g of aramid precipitate with a beating degree of 45°SR and a water content of 85%, weighing 0.50g of conductive carbon black with a conductivity of 0.20S·cm-1, weighing 0.3766g of carbon fiber with a fiber length of 3mm and a fiber diameter of 6 microns and 10.00mL of a PEO dispersion with a concentration of 10g / L and adding them into a deflaking cylinder in sequence; obtaining a mixed system slurry A by a deflaking treatment at a rotation number of 30000 rpm, and then adding 3.0L of dilution water, performing 10 times of turbulent homogenization and 25 seconds of negative pressure dehydration on an 80-mesh forming wire to form a surface layer wet paper web B.

[0037] 0.8795 g of carbon fiber with a fiber length of 7 mm and a diameter of 6 microns was weighed, and 2.1863 g of aramid precipitate with a beating degree of 45°SR and a water content of 85% was weighed and mixed with 10.00 mL of a PEO dispersion with a concentration of 10 g / L. A mixed slurry C was obtained by degassing at 30,000 rpm, and then 3.0 L of dilution water was added, 10 times of turbulent homogenization and 25 seconds of negative pressure dehydration on an 80-mesh forming wire were performed to form a surface wet paper web D.

[0038] Step 2: transfer the middle layer wet paper web D to the middle of the two surface layer wet paper webs B, overlap them, pad them with absorbent felt on the top and bottom, and use a cold press with a pressing pressure of 9.0 MPa to dehydrate for 5 minutes to obtain paper web E.

[0039] Step 3, vacuum dry the paper web E in the drying section of a paper sheet former at a temperature of 105°C and a vacuum degree of 0.8MPa for 10 minutes; and hot-press and bond it in a flat vulcanizer at a temperature of 200°C and a pressure of 13MPa for 15 minutes to obtain a hierarchical asphalt-based carbon fiber skeleton electric heating base paper F.

[0040] The hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper obtained in this embodiment (such as Figure 6 , 7 , 8), the paper weight is 40g / m 2 , thickness is 0.175mm, square resistance is 19.49Ω, tensile strength is 1.13kN / m, paper weight is 4.53g, it can be heated to 250℃ at 12V voltage, heating rate is 2.27℃ / s, and it has high electric heating function under low voltage. Fig. 9 The surface temperature of carbon fiber paper containing 0.5g carbon black increases with the increasing voltage. At 4V, the surface temperature can reach 40℃; at 8V, the surface temperature can reach 140℃; at 12V, the surface temperature can reach 250℃.

[0041] Fig.10 and Fig.11The temperature curve changing with time shows three processes: heating, stable heating and power off / power off cooling. It can be seen that the heating performance or saturation temperature of carbon fiber paper can be adjusted by simply controlling the carbon black content in the carbon fiber paper and the supply voltage.

[0042] Fig.12 The XRD spectra of carbon fiber paper containing 0.3g and 0.5g carbon black show sharper peaks in the XRD graph, indicating that the carbon fiber microstructure in the sample is more regular. It can be seen from the figure that the carbon fiber has a broad peak at 2θ=26.25° and 26.18°, corresponding to the graphite (002) crystal plane, indicating that the carbon atoms are connected to each other in an sp² hybrid manner.

[0043] Figure 7 , 8 The cross-section and surface SEM magnified images of the carbon fiber paper obtained in Examples 1 and 2 respectively show that the carbon fibers are evenly wound and connected.

[0044] Example 3 Step 1, weighing 0.2600g of aramid pulp with a beating degree of 45°SR and a specific surface area of ​​9m² / g, weighing 3.6400g of aramid precipitate with a beating degree of 42°SR and a water content of 70%, weighing 0.30g of conductive carbon black with a conductivity of 0.20S·cm-1, weighing 0.3700g of carbon fiber with a fiber length of 3mm and a fiber diameter of 6 microns and 10.00mL of a PEO dispersion with a concentration of 10g / L and adding them into a deflaking cylinder in sequence; obtaining a mixed system slurry A by a deflaking treatment at a rotation number of 30000 rpm, and then adding 2.0L of dilution water, performing 8 times of turbulent homogenization and 20 seconds of negative pressure dehydration on an 80-mesh forming wire to form a surface layer wet paper web B.

[0045] 0.8700 g of carbon fiber with a fiber length of 7 mm and a diameter of 6 microns was weighed, and 2.1800 g of aramid precipitate with a beating degree of 45°SR and a water content of 85% was weighed and mixed with 10.00 mL of a PEO dispersion with a concentration of 10 g / L. A mixed slurry C was obtained by degassing at 30,000 rpm, and then 2.0 L of dilution water was added, 8 turbulent homogenizations were performed, and 20 seconds of negative pressure dehydration treatment was performed on an 80-mesh forming wire to form a surface wet paper web D.

[0046] Step 2: transfer the middle layer wet paper web D to the middle of the two surface layer wet paper webs B, overlap them, pad them with absorbent felt on the top and bottom, and use a cold press with a pressing pressure of 8.5 MPa to dehydrate for 5 minutes to obtain paper web E.

[0047] Step 3, vacuum dry the paper web E in the drying section of a paper sheet former at a temperature of 105°C and a vacuum degree of 0.7MPa for 10 minutes; and hot-press and bond it in a flat vulcanizer at a temperature of 180°C and a pressure of 12MPa for 15 minutes to obtain a hierarchical asphalt-based carbon fiber skeleton electric heating base paper F.

[0048] The hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper in this embodiment has a basis weight of 40g / m 2 , thickness is 0.138mm, square resistance is 20.11Ω, tensile strength is 1.03kN / m, paper weight is 4.30g, it can be heated to 187℃ at 12V voltage, with a heating rate of 1.98℃ / s, and has high electric heating function under low voltage.

[0049] Example 4 Step 1, weighing 0.2650g of aramid pulp with a beating degree of 46°SR and a specific surface area of ​​10m² / g, weighing 3.6452g of aramid precipitate with a beating degree of 43°SR and a water content of 80%, weighing 0.40g of conductive carbon black with a conductivity of 0.40S·cm-1, weighing 0.3754g of carbon fiber with a fiber length of 3.5mm and a fiber diameter of 8 microns and 10.50mL of a PEO dispersion with a concentration of 13g / L and adding them into a deflaking cylinder in sequence; obtaining a mixed system slurry A by a deflaking treatment at a rotation speed of 30000 rpm, and then adding 2.5L of dilution water, performing 9 times of turbulent homogenization and 22 seconds of negative pressure dehydration on a 90-mesh forming wire to form a surface layer wet paper web B.

[0050] 0.8751 g of carbon fiber with a fiber length of 7.5 mm and a diameter of 8 microns was weighed, 2.1853 g of aramid precipitate with a beating degree of 48°SR and a water content of 89% was weighed and mixed with 10.50 mL of a PEO dispersion with a concentration of 13 g / L, and a mixed slurry C was obtained by degassing at 30,000 rpm. 2.5 L of dilution water was added, 9 turbulent homogenizations were performed, and negative pressure dehydration treatment was performed on a 90-mesh forming wire for 23 seconds to form a surface wet paper web D.

[0051] Step 2: transfer the middle layer wet paper web D to the middle of the two surface layer wet paper webs B, overlap them, pad them with absorbent felt on the top and bottom, and use a cold press with a pressing pressure of 9.0 MPa to dehydrate for 8 minutes to obtain paper web E.

[0052] Step 3, vacuum dry the paper web E in the drying section of a paper sheet former at a temperature of 110°C and a vacuum degree of 0.8MPa for 12 minutes; and hot-press and bond it in a flat vulcanizer at a temperature of 190°C and a pressure of 13MPa for 18 minutes to obtain a hierarchical asphalt-based carbon fiber skeleton electric heating base paper F.

[0053] The hierarchical asphalt-based carbon fiber skeleton electric heating base paper obtained in this example has a basis weight of 40 g / m 2 , thickness is 0.152mm, square resistance is 19.24Ω, tensile strength is 1.15kN / m, paper weight is 4.46g, it can be heated to 249℃ at 12V voltage, heating rate is 2.25℃ / s, and it has high electric heating function under low voltage.

[0054] Example 5 Step 1, weighing 0.2700g of aramid pulp with a beating degree of 48°SR and a specific surface area of ​​11m² / g, weighing 3.6500g of aramid precipitate with a beating degree of 45°SR and a water content of 85%, weighing 0.50g of conductive carbon black with a conductivity of 0.50S·cm-1, weighing 0.3800g of carbon fiber with a fiber length of 4mm and a fiber diameter of 10 microns and 11.00mL of a PEO dispersion with a concentration of 15g / L and adding them to a deflaking cylinder in sequence; obtaining a mixed system slurry A by a deflaking treatment at a rotation number of 30000 rpm, and then adding 3.0L of dilution water, performing 10 times of turbulent homogenization and 25 seconds of negative pressure dehydration on a 100-mesh forming wire to form a surface layer wet paper web B.

[0055] 0.8800 g of carbon fiber with a fiber length of 8 mm and a diameter of 10 microns was weighed, and 2.1900 g of aramid precipitate with a beating degree of 50°SR and a water content of 92% was weighed and mixed with 11.00 mL of a PEO dispersion with a concentration of 15 g / L. A mixed slurry C was obtained by degassing at 30,000 rpm, and then 3.0 L of dilution water was added, 10 turbulent homogenizations and 25 seconds of negative pressure dehydration on a 100-mesh forming net were performed to form a surface wet paper web D.

[0056] Step 2: transfer the middle layer wet paper web D to the middle of the two surface layer wet paper webs B, overlap them, pad them with absorbent felt on the top and bottom, and use a cold press with a pressing pressure of 10.5 MPa to dehydrate for 10 minutes to obtain paper web E.

[0057] Step 3, vacuum dry the paper web E in the drying section of a paper sheet former at a temperature of 110°C and a vacuum degree of 0.9 MPa for 15 minutes; and hot-press and bond it in a flat vulcanizer at a temperature of 200°C and a pressure of 15 MPa for 20 minutes to obtain a hierarchical asphalt-based carbon fiber skeleton electric heating base paper F.

[0058] The hierarchical asphalt-based carbon fiber skeleton electric heating base paper obtained in this embodiment has a paper basis weight of 40g / m2, a thickness of 0.181mm, a square resistance of 17.43Ω, a tensile strength of 1.18kN / m, a finished paper weight of 4.61g, can be heated to 282°C at a voltage of 12V, and a heating rate of 2.35°C / s, and has high electric heating function under low voltage.

[0059] Table 1 Technical parameters of hierarchical asphalt-based carbon fiber skeleton electric heating base paper prepared by the implementation case

[0060] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper, characterized in that: The following steps are involved: S1, preparing a surface paper web: weighing aramid pulp, aramid precipitate, conductive carbon black, carbon fiber and PEO dispersion, mixing and dispersing to obtain a mixed system slurry A, and then forming a surface wet paper web B by slurry dilution, turbulent homogenization and negative pressure dehydration; Preparation of middle layer paper web: weighing carbon fiber, aramid precipitate and PEO dispersion, mixing and dispersing to obtain mixed slurry C, and then forming carbon fiber middle layer wet paper web D by dilution, water addition, turbulent homogenization and negative pressure dehydration; S2, overlapping the middle layer wet paper web D and the surface layer wet paper web B, and then cold pressing and dehydrating to obtain a layered structure paper web E; S4, subjecting the hierarchical structure paper web E to vacuum drying and hot pressing bonding to obtain a hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper F.

2. The process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S1, when preparing the surface paper web, the aramid pulp is para-aramid fiber, the beating degree is (45-48)°SR, the specific surface area is (9-11) m² / g, and the total absolute dry weight is (0.26-0.27) g; The aramid precipitate is a differentiated product of meta-aramid fiber, with a beating degree of (42-45)°SR, a moisture content of (70-85)%, and a total absolute dry weight of (3.64-3.65) g; The carbon fiber is pitch-based carbon fiber, with a fiber length of (3-4) mm, a fiber diameter of (6-10) μm, and a total absolute dry weight of (0.37-0.38) g; the mass of the conductive carbon black is (0.30-0.50) g, and the electrical conductivity is (0.20-0.50) S·cm-1; The concentration of PEO dispersion is (10-15) g / L, and the measured volume is (10.00-11.00) mL.

3. The process for preparing hierarchical asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S1, when preparing the surface paper web, the deflaking rotation speed is 25000~30000 rpm; The amount of water added for dilution is (2.0~3.0)L; Turbulent homogenization is (8-10) times; Water is vacuumed through a (80-100) mesh forming net, the vacuum degree is 0.080-0.098 MPa, and the vacuum pumping time is (20-25) s.

4. The process for preparing hierarchical asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S1, when preparing the middle layer paper web, the carbon fiber is asphalt-based carbon fiber, the fiber length is (7-8) mm, the fiber diameter is (6-10) microns, and the total absolute dry weight is (0.87-0.88) g; The aramid precipitate is a differentiated product of meta-aramid fiber, with a beating degree of (45-50)°SR, a moisture content of (85-92)%, and a total absolute dry weight of (2.18-2.19) g; The concentration of the PEO dispersion is (10-15) g / L, and the measured volume is (10.00-11.00) mL.

5. The process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S1, when preparing the middle layer paper web, the deflaking rotation number is 25000~30000 rpm; The amount of water added for dilution is (2.0~3.0)L; Turbulent homogenization is (8-10) times; Water is vacuumed through a (80-100) mesh forming net, the vacuum degree is 0.080-0.098 MPa, and the vacuum pumping time is (20-25) s.

6. The process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S2, when overlapping, the middle layer wet paper web D is transferred between the two surface layer wet paper webs B.

7. The process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S2, during cold pressing and dehydration, absorbent felt pads are used on the upper and lower sides of the superimposed wet paper webs, the pressing pressure is (8.5~10.5) MPa, and the pressing time is (5~10) min.

8. The process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S3, during the vacuum drying process, the temperature is (105-120)°C, the vacuum degree is (0.7-0.9) MPa, and the time is (10-15) min.

9. The process for preparing hierarchical structure asphalt-based carbon fiber skeleton electric heating base paper according to claim 1, characterized in that: In S3, during the heat-pressing bonding treatment, the temperature is (180-200)°C, the pressure is (12-15) MPa, and the time is (15-20) min.

10. A product obtained by the process for preparing hierarchical asphalt-based carbon fiber skeleton electric heating base paper according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Industrial high-temperature carbon fiber electric heating paper and making method thereof

    CN102465475A

  • A flame-retardant carbon fiber electrothermal paper and its preparation method

    CN103628350B

  • A carbon fiber paper for fuel cells and its preparation method

    CN110129992B

  • Multiple proportional layered composite manufactured amide paper of aramid fiber

    CN101003959A

  • Carbon fiber paper with conductive network enhanced by carbon black and preparation method of carbon fiber paper

    CN114164709A